Antidiabetic Effects of Physical Activity: How It Helps to Control Type 2 Diabetes - Wake AD (Dove Medical Press, 2020)
Addisu Dabi Wake Nursing Department, College of Health Sciences, Arsi University, Assela, Oromia, EthiopiaCorrespondence: Addisu Dabi WakeNursing Department, College of Health Sciences, Arsi University, P.O. Box: 393/04, Asella, EthiopiaTel +251 910 2867 66Email addansa12@gmail.comAbstract: Despite the improvements in clinical care of the patients, research updates, and public health interventions, there is still an increase in the prevalence, incidence, and mortality because of diabetes mellitus (DM). DM is a public health problem in both developed and developing countries. It has increased alarmingly, putting this disease in the dimension of an epidemic. Diabetes is associated with several complications which increase the risk of many serious health problems on the other side. Therefore, this review was aimed to discuss the antidiabetic effects of physical activity (PA) on type 2 DM (T2DM) by summarizing the significant studies on this topic. This review found that several studies have recommended the utilization of PA for the effective management of T2DM. PA is a non-pharmacologic therapy which is a significant strategy for the management of T2DM and is an appropriate lifestyle modification approach to be practiced by these patients. The studies showed that PA has antidiabetic effects which are evidenced by its substantial role in improving the blood glucose (BG) levels of the individuals with T2DM where it helps them to control their levels of glucose in the blood. It plays a significant role in glycemic control of this disease by lowering the BG levels through possible mechanisms such as decreasing insulin resistance, increasing production of glucose transporter type 4 (GLUT-4), lowering visceral adipose tissue (VAT), increasing pancreatic β-cell functions, using glucose for energy, and so on. In turn, the controlled glycemia helps to prevent the complications associated with uncontrolled T2DM and this would further improve the overall health of the patients and the burden on the health professionals as well. Finally, this review concludes that PA is the cornerstone in the management of T2DM. It also suggests that more attention is needed to its significance in the prevention, glycemic control, and its role in the management of the morbidity and mortality associated with T2DM. Practical PA recommendations and suggestions for the future direction of research in this area are also provided.Keywords: diabetes mellitus, physical activity, exercise, glycemic control, type 2 diabetes